2018
DOI: 10.1097/wnr.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence of language switching for bidialectals

Abstract: Language switching is an important issue in the study of bilinguals. However, how the nontarget language affects the production of the target language under the language switch condition is still unclear, especially for bilinguals who speak two dialects (bidialectals). In the present study, we investigate this issue by a picture-naming task and using an event-related potential (ERP) technique. Two groups of proficient bidialectals, Mandarin (L1)-Cantonese (L2) and Cantonese (L1)-Mandarin (L2), participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, the correlations between some of the factors were greater than 0.85, suggesting poor identification of factor entries and suggesting merging or modifying the form of topic presentation. For example, the correlations between spontaneous expression and orientation, transient memory, and delayed recall; orientation and computation, and delayed recall; computation and retelling, reading, and memory; and transient memory and delayed recall were all greater than 0.85, and the following reasons were considered: on the one hand, it is possible that correlations greater than 0.85 were consistent with the linguistic neuropsychological pathway at the time of question presentation; in addition, linguistic cognition is inextricably linked (Yi, Chen, Chang, Wang, & Wu, 2018), transient memory is highly correlated with delayed recall, as the measured are memory topics, and the memory capacity and length are consistent. The computational factor was examined by asking the subjects to listen and say the corresponding answer, and the computational questions covered the expression and memory-related factor components.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlations between some of the factors were greater than 0.85, suggesting poor identification of factor entries and suggesting merging or modifying the form of topic presentation. For example, the correlations between spontaneous expression and orientation, transient memory, and delayed recall; orientation and computation, and delayed recall; computation and retelling, reading, and memory; and transient memory and delayed recall were all greater than 0.85, and the following reasons were considered: on the one hand, it is possible that correlations greater than 0.85 were consistent with the linguistic neuropsychological pathway at the time of question presentation; in addition, linguistic cognition is inextricably linked (Yi, Chen, Chang, Wang, & Wu, 2018), transient memory is highly correlated with delayed recall, as the measured are memory topics, and the memory capacity and length are consistent. The computational factor was examined by asking the subjects to listen and say the corresponding answer, and the computational questions covered the expression and memory-related factor components.…”
Section: Discussionmentioning
confidence: 99%
“…This last study suggests that there may be a specific language control system associated with diglossia. Studies on dialect switching in diglossic speakers showed both behavioral slowing and electrophysiological activation during switching between dialects [50] in regions such as the left DLPFC, ACC IPL and basal ganglia [51,52]. Yi et al [50] suggest the implication of the language control system when switching between dialects.…”
Section: Of 16mentioning
confidence: 99%
“…When it comes to trial design, seven out of ten studies did not rely on stimulus timing jittering (71.1%) or measures to prevent overlap between motor response and ERP components (52.3%), to reduce sources of noise in ERP recordings. Examples of measures used to prevent overlap between motor response and ERP components included a cue for participants to respond only after the ERP time window had passed (which is efficient only if combined with jittering the cue because of preparatory motor activity) and designs (Yi et al, 2018) in which there was no overt response to stimuli used in the N400 analyses, either because overt responding was not required or because the participants responded to other stimuli. When it comes to artifact elimination method, 62.4% papers reported rejecting all types of artifacts which were detected.…”
Section: How Muchmentioning
confidence: 99%